THE STRATEGIC ROLE OF ACCOUNTING INFORMATION SYSTEMS IN ENHANCING THE EFFECTIVENESS OF BUDGET PREPARATION AND IMPLEMENTATION - Masrullah, Masrullah; Putri P, Andi Sri Kumala; Nirwana, Nirwana; Indrijawati, Aini (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to examine the role of Accounting Information Systems in the preparation and implementation of budgets at the Department of Trade and Industry of Gowa Regency. Accounting Information Systems play an important role in providing accurate, relevant, and timely information to support decision-making processes, particularly in budget management within government institutions. The research employed a qualitative descriptive method. The types of data used in this study consisted of primary and secondary data. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through the processes of data collection, data reduction, data presentation, and conclusion drawing. The results of the study indicate that Accounting Information Systems play a significant role in supporting the budget preparation process through the provision of integrated and systematic data. Furthermore, in budget implementation, Accounting Information Systems assist in recording, reporting, and budget control processes, thereby improving the effectiveness and efficiency of financial management. Nevertheless, several obstacles remain, including limitations in human resources and the suboptimal utilization of the system.